Tetrapod axial evolution and developmental constraints; Empirical underpinning by a mouse model - Woltering, Joost M.; Duboule, Denis (Mechanisms of development, 2015)
The tetrapod vertebral column has become increasingly complex during evolution as an adaptation to a terrestrial life. At the same time, the evolution of the vertebral formula became subject to developmental constraints acting on the size of the cervical and thoraco-lumbar regions. In the course of our studies concerning the evolution of Hox gene regulation, we produced a transgenic mouse model expressing fish Hox genes, which displayed a reduced number of thoraco-lumbar vertebrae and concurrent sacral homeotic transformations. Here, we analyze this mutant stock and conclude that the ancestral, pre-tetrapodial Hox code already possessed the capacity to induce vertebrae with sacral characteristics. This suggests that alterations in the interpretation of the Hox code may have participated to the evolution of this region in tetrapods, along with potential modifications of the HOX proteins themselves. With its reduced vertebral number, this mouse stock violates a previously described developmental constraint, which applies to the thoraco-lumbar region. The resulting offset between motor neuron morphology, vertebral patterning and the relative positioning of hind limbs illustrates that the precise orchestration of the Hox-clock in parallel with other ontogenetic pathways places constraints on the evolvability of the body plan. •A transgenic mouse line expressing fish Hox genes has anterior homeotic transformations.•Fish Hox genes are capable of inducing tetrapod specific vertebral characters.•A sacral Hox-code influences adult hindlimb position, yet not the position of limb budding.